Desenvolvimento regional sustentável: avaliação da política FNE Sol e seus reflexos no estado do Ceará, nordeste do Brasil - Silva, Carlos Hugo Carvalho (2023)
The intense global concern with the energy issue has raised several questions, especially the environmental ones, about the impacts promoted in their generation matrices. In this context, the present work aims to evaluate the process of functioning of the public policy FNE Sol in the state of Ceará, since the beginning of its operation by Banco do Nordeste do Brasil (BNB), in the year 2016, until 2022. The FNE Sol, as a public policy that makes up the Northeast Financing Constitutional Fund (FNE) in favor of collaborating with the objectives of the National Regional Development Policy (PNDR), is based on the premise of using public resources to finance projects that encourage the production of energy from renewable sources, with emphasis on the photovoltaic solar array. It is an exploratory and quantitative-qualitative research, carried out from the evaluative path of public policies called Evaluation based on Sustainability (ABS). This proposal seeks to evaluate a public policy in all its cycles, in an interdisciplinary and organic way, from the perspective of sustainable development and its sustainability dimensions. Priority was given to documental and bibliographic materials from sources, academic, public and private institutions, as well as some information available on the internet, always favoring the sieve of representativeness for the renewable energy sector. The fact of not having adopted sustainability criteria in the construction and implementation, ended up perpetuating the economicist bias in the FNE Sol in a very notorious way, thus disregarding its due importance in the face of the social and environmental perspectives. This finding shows the importance of determining, in an innovative way, an assessment based on sustainability dimensions, in order to contribute to the increment of regional development with fairer economic growth, minimizing environmental damage and generating benefits for society. From the above, it was possible to conclude that photovoltaic solar energy is the sustainable alternative that grows the most in the world and in Brazil, especially due to the increase coming from the Northeast region, which is considered one of the main protagonists in the sector. And the state of Ceará is a great national exponent in the photovoltaic rankings, still with a lot of potential to be explored. However, the way in which the FNE Sol has been conducted and operated by the BNB, despite its improvements over the years, places it far below its expected potential. The lack of dynamism in relation to social and productive sector demands, as well as excessive state bureaucracy, end up causing obstacles that do not allow the program to fully achieve its objectives as a public policy for sustainable regional development.